Evaluasi SIM-RS menggunakan Metode TAM (Technology Acceptance Model) di Ruang Rawat Inap Rumah Sakit Umum Cut Meutia Kota Langsa Tahun 2025 - Nadya Isnaini; Zulkhairi Zulkhairi (Pusat Riset dan Inovasi Nasional, 2025)
Evaluation measures work or things that are done, evaluation is very useful or useful because it can determine the level of work and also as an assessment of what has been done or done. Management Information Systems are a network of data processing procedures developed within an organization and approved when necessary to provide data to management as a basis for decision making in order to achieve goals. This research aims to determine the relationship between SIMRS Evaluation and the TAM (Technology Acceptance Model) Method. This type of research is analytical, with a cross sectional design, this research uses independent variables, namely perceived Ease of Use and Attitude Toward Using, technically it also uses an independent variable, namely SIMRS Evaluation. With a total sample of 52 respondents using accidental sampling technique. Data were analyzed univariately and bivariately with chi square presented in the form of a frequency distribution table. The results of the research concluded that of the 52 respondents, the majority were Good, 23 respondents (44.2%) while the majority were Not Good, namely 29 respondents (55.8%). There is a relationship between the SIMRS Evaluation of Convenience in the Cut Meutia Langsa General Hospital Inpatient Installation with a P-value of 0.000 (p<0.05). and there is a relationship between the SIMRS Evaluation of Attitudes in the Cut Meutia Langsa General Hospital Inpatient Installation with a p-value of 0.000 (p<0.05). The conclusion of this research is that the Cut Meutia Langsa General Hospital can carry out regular structural evaluations of officers in operating SIMRS.